FK506 to prevent lung injury after hindlimb ischemia and reperfusion in a rat model: An electron microscopic study - ŞİRVANCI, SERAP; ARSAN, SİNAN (SPRINGER, 2004)
Purpose. Hindlimb ischemia and reperfusion leads to lung injury in various animal models. We investigated the effectiveness of FK506, an immunosuppressive agent, which also modulates neutrophilic infiltration, in preventing lung injury after hindlimb ischemia and reperfusion in a rat model. Methods. Twenty-seven male Sprague-Dawley rats were randomized to received FK506 at doses of 0.3 mg/kg, 0.5 mg/kg, or 1 mg/kg body weight per day, or normal saline injections, as pretreatment, and there was also a sham group. On the 4th day, the animals were subjected to 2 h of ischemia induced by a tourniquet, followed by reperfusion of the extremities for 2 h. Lung tissue assays were performed for the lipid peroxidation product malondialdehyde (MDA) and total glutathione (GSH). Lung tissues were also examined histopathologically under light and electron microscopy. Results. The MDA levels in the study groups were significantly lower than those in the control group (P < 0.05), but the total GSH levels did not differ significantly among the groups. Histopathologically, there were no significant differences among the groups given different doses of FK506, but there was a significant difference between the control group and all the treatment groups. Conclusion. FK506 ameliorates the lung injury associated with ischemia and reperfusion of the lower limbs, and might have an inhibitory effect on the neutrophils that cause remote organ damage.
Keywords: ischemia-reperfusion injury; lung; extremities; NEUTROPHIL INFILTRATION; LIMB ISCHEMIA; FREE-RADICALS; SKIN FLAPS; CYCLOSPORINE; LIVER